ANALISIS KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN BIOLOGI PADA MATERI VIRUS KELAS XI SMAN 5 SAMARINDA PADA TAHUN AJARAN 2023/2024 - Karimah, Aulia; Masitah, Masitah; Herliani, Herliani; Purwati, Sri (Jurnal Review Pendidikan dan Pengajaran, 2024)
Analysis of Student Learning Difficulties in Learning Biology on Virus Material for Class XI SMAN 5 Samarinda in the 2023/2024 Academic Year. This research aims to describe and analyze learning difficulties and the factors that cause students' learning difficulties in viral material. This research uses a descriptive method with a quantitative approach. The technique used in sampling in this research was purposive sampling with classes XI-2 and XI-3. The data analysis method in this research is descriptive statistics for analysis. The results of this research show that the factors causing students' learning difficulties come from internal factors amounting to 69% and external factors amounting to 65% belonging to the high influential criteria. The factor that causes the highest learning difficulties from internal factors is the talent indicator at 79%, while the factor that causes the highest learning difficulties from external factors is the teacher-student relationship indicator at 77%.